2019
DOI: 10.1017/dsi.2019.163
|View full text |Cite
|
Sign up to set email alerts
|

Purpose-Oriented Modelling of the Learning Process When Using Prototypes

Abstract: Prototypes are often used as a tool in the product development process and their usage is advised in many guidelines, frameworks and product development methods. Those prototypes achieve different goals of which most relate to getting new insights and information about the product in development. For the development of those prototypes however, significantly less development methods are available compared to the number of methods for the development of products. Investigating the process of using a prototype l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Schork et al [178] proposed two concepts for sensor-integrating not shiftable, flexible, interlocking couplings: i) a helical beam coupling for the measurement of shaft misalignments and ii) a concept for an elastic jaw coupling. The advantage of the helical beam coupling for sensor integration is the fact that it has a relatively large installation space for the electronics due to the cavity, which is even partially capsuled.…”
Section: Couplingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schork et al [178] proposed two concepts for sensor-integrating not shiftable, flexible, interlocking couplings: i) a helical beam coupling for the measurement of shaft misalignments and ii) a concept for an elastic jaw coupling. The advantage of the helical beam coupling for sensor integration is the fact that it has a relatively large installation space for the electronics due to the cavity, which is even partially capsuled.…”
Section: Couplingsmentioning
confidence: 99%
“…By applying strain gauges on the plate the deformation can be measured. Schork et al [178] found that angular displacement can be reliably measured, whereas radial displacement can only be determined inadequately. For the elastic jaw coupling, they integrated a bending plate, with applied strain gauges in one tooth of the gear rim, in order to measure the deformation of the tooth.…”
Section: Couplingsmentioning
confidence: 99%
“…In addition, the process of prototyping serves as a valuable tool for assessing the potential manufacturability and production feasibility of a given physical product [49]. The development of prototypes that bear a strong resemblance to the ultimate product enables teams to evaluate a range of factors, including material compatibility, assembly processes, and cost considerations [50]. The prompt detection of manufacturing limitations or obstacles confers upon teams the ability to effectuate requisite design adjustments, thereby guaranteeing a seamless progression from prototype to production.…”
Section: Agile Physical Product Developmentmentioning
confidence: 99%